Child development students’ perspectives on organic animal products: knowledge, attitudes and behaviors - Aral, Oğulcan; Cufadar, Yusuf; Kadan, Gül; Aral, Neriman; Aysu, Burçin (Frontiers in Nutrition, 2025)
Organic nutrition and its variant organic animal products constitute one of the most important areas of nutrition today. The consumption of organic animal products, which are known to make significant contributions to strengthening the immune system and ensuring a balanced and adequate diet, becomes even more important, especially for the development of children. For this reason, it is necessary to determine the extent of knowledge of child development specialist candidates, who work with children and families and have significant effects on children’s development, about organic animal products. Based on this idea, the aim of the research was to examine the knowledge, attitudes and behaviors of university students studying at universities that provide associate and undergraduate child development education in Türkiye through the screening method. The screening model, which is one of the quantitative research methods, was used in the study and it was conducted with the students of the child development department who continue their associate and undergraduate education in the child development program throughout Türkiye. The data were collected with the “Knowledge, Attitude and Behavior Survey Form for Organic Animal Products” developed by Aral and Çufadar. As a result of the study, it was determined that the scores of male students, those with a birth date of 2000 and below, associate degree students, those who know organic products, those who consume organic products, and those who look at the certificate when buying organic products were significantly higher in the behavioral dimension. In addition, in the attitude dimension, it was also found that the scores of those with a birth date of 2000 and below, those who consume organic products and have knowledge about organic products, those who look at the certificate when buying organic products and associate degree students were significantly higher. Moreover, it was concluded that there was a weak relationship between knowledge and behavior dimensions and attitude dimension. Based on the results obtained from the study, it can be suggested that students should be informed about organic animal products and necessary measures should be taken to facilitate access to these products.